Analysis of Career Planning Ability Level of Vocational High School Students - Fedrina, Fedrina Aysia Dewi Saputri; Juliejantiningsih, Yovitha (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study is based on the background that the results of the questionnaire of students' needs that I gave to class XI, especially in class XI, there were 3.16% of students who were still uncertain about their choice of goals, 3.31% of students who still did not understand the study program in college, and there were 2.86% of students who did not understand the relationship between talent, interest, education, and work. The research method used is a survey research method with a quantitative approach that aims to reveal what it is. The population in this study were all students of class XI of SMK Negeri 4 Semarang. The results showed that career planning ability can be known that the lowest score was 15 respondents in the very high category with a percentage of 19%, 22 respondents in the high category with a percentage of 28%, 43 respondents in the medium category with a percentage of 54%, 0 respondents in the low category with a percentage of 0%, and 0 respondents in the very low category with a percentage of 0%. Suggestions that researchers can convey should guidance and counseling teachers have played an active role but guidance and counseling teachers must develop or improve career guidance services at school.